Exploration and Identification of Siamese Orange (Citrus nobilis Lour.) Plant diversity in Banyuwangi Regency - Anisah, Siti Nur; Nofi Utari (Jurnal Biologi Tropis, 2025)
Siamese orange (Citrus nobilis Lour.) is a horticultural product with significant economic importance in Indonesia. This study aims to identify the diversity of accessions of Siamese orange plants spread in Banyuwangi Regency, which is one of the main citruses producing areas in Indonesia. Exploration activities were carried out in several sub-districts with high potential for citrus cultivation. Data collection was carried out through direct field observations and interviews with local farmers, as well as morphological identification based on leaf, stem and fruit characteristics. The results showed that from five research locations, 2 clusters were obtained, which were concluded in 1 cluster as a group of Siamese orange accessions with phenotypic characters suitable for producing citrus fruits. There is significant morphological variation among Siamese citrus populations, especially in leaf and stem morphology. This variation reflects the genetic richness of local Siamese oranges that have the potential to be developed as superior varieties. This study provides important basic information for the preservation of genetic resources and the development of a breeding program for Siamese oranges in Banyuwangi.